Routing Protocols for Wireless Mesh Networks: A survey - KN, Prema KN; MB, Ushadevi MB (International Journal of Computer Sciences and Engineering, 2019)
In present the quickening pace of technological change development Wireless technology is growing in broad, there are many research issues arises in the wireless technology, the fundamental requirement in wireless is routing. Wireless mesh network is the emerging technology in which routing is the fundamental characteristic of the wireless network. Wireless mesh networks are very much capable of providing internet access anywhere anytime for stationary or mobile hosts at low costs both for network operators and customers. In wireless networks Routing is the necessary fundamental characteristics .In WMNs routing is the challenging research area due to the occurrence of unexpected changes in the wireless environments. There exist two different ways to enhance the performance of routing protocols in wireless networks. In wireless mesh network have to improve the metric used in the selection path , to modify the routing algorithms by considering new characteristics of the network and can apply cross-layer approach by merging the characteristics of two or more layers. This paper discussed about various types of routing protocols that are used in the wireless mesh networks along with metrics that are used in wireless mesh networks.